PROBLEMS OF A FAMILY, RAISING A CHILD WITH SPECIAL NEEDS (EDUCATION IN THE 21ST CENTURY, 2023)
The present article reveals the main problems of parenting a child with developmentaldisabilities. It is known, that the upbringing, education and development of a child starts in thefamily. However, the solution of these essential tasks is significantly complicated in a familyraising a child with various developmental disabilities.The success of this study depends on how well parents are informed about thepsychophysical characteristics of the child's development; about using the means, methods andconditions for organizing and conducting therapeutic, recreational and core-developmentalactivities in a family.This defines the necessity to study the problem of a family raising a child with developmentaldisabilities.In the general system of upbringing and educating a child with special needs, the role of thefamily and the awareness of parents in these matters is immeasurably increasing. The specialscientific and methodological literature emphasizes the importance of studying the problem ofparenting a child with developmental disabilities, providing informational assistance to parents inraising those children in a family environment. However, insufficient knowledge of the problem ofa family raising a child with developmental disabilities significantly complicates the effectivesolution of many issues of this problem. The foregoing defines the relevance of this study, itstheoretical and practical significance.
Keywords: family, child with developmental disabilities, parents, upbringing, education, child development, difficulties in education, family problems, parental awareness